RETRACTED: Environmental legislation of Kyrgyzstan problems and solutions - Zhusupov Bolotbek; Kuldysheva Gulsara; Istamkulov Japar (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001